2022
DOI: 10.3390/nano12071152
|View full text |Cite
|
Sign up to set email alerts
|

Convective Heat Transfer Analysis for Aluminum Oxide (Al2O3)- and Ferro (Fe3O4)-Based Nano-Fluid over a Curved Stretching Sheet

Abstract: In this work, the combined effects of velocity slip and convective heat boundary conditions on a hybrid nano-fluid over a nonlinear curved stretching surface were considered. Two kinds of fluids, namely, hybrid nano-fluid and aluminum oxide (Al2O3)- and iron oxide (Fe3O4)-based nano-fluid, were also taken into account. We transformed the governing model into a nonlinear system of ordinary differential equations (ODEs). For this we used the similarity transformation method. The solution of the transformed ODE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Shehzad et al [32] identified the analysis of heat flux in ferromagnetic fluid with titanium no-particles effects. e related work of ferrofluid can be seen in references [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Shehzad et al [32] identified the analysis of heat flux in ferromagnetic fluid with titanium no-particles effects. e related work of ferrofluid can be seen in references [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The heat transfer modeling in stratified flow of ferrofluid over a stretching sheet was demonstrated by Noor et al [15]. Ashraf et al [16] explored the combination of momentum slip phenomena in hybrid nanofluid by considering curved sheet. The nonlinear thermal radiating flow of ferrofluids over a moving plate with magnetic dipole effects was identified by Ali et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Anusha, T., Mahabaleshwar, U.S. and Sheikhnejad, Y (4) explained the work on 2D laminar magnetohydrodynamics couple stress hybrid nanofluid is performed with inclined magnetic field over the stretching/shrinking surface embedded in porous media. Ashraf A, Zhang Z, Saeed T, Zeb H, Munir T (5) . studied the combined effects of velocity slip and convective heat boundary conditions on a hybrid nanofluid over a nonlinear curved stretching surface.…”
Section: Introductionmentioning
confidence: 99%